The Potential Of Hybrid Turbine Ventilator To Improve Indoor Climatic Conditions In Hot-Humid Environment - Ismail, Mazran (2010)

(untitled)
This thesis presents the results of the empirical studies regarding the possibilities of improving indoor climatic conditions in the hot-humid environment with the use of hybrid turbine ventilator (HTV). From the literature, it is found that the fan assisted stack ventilation strategy like the HTV is one of the most potent strategies to be applied in this high solar radiation and low wind velocity region of Malaysia. Through the pilot experiment study, an optimum configuration of the HTV has been determined, which is the new configuration with inner duct and larger free upper outlet area is found to show the best performance in inducing indoor air movement. Then, a series of full-scale field measurement studies conducted in the real building and under real weather conditions confirmed the significance of the device in improving indoor climatic conditions. The study shows that the strategy of applying HTV for occupied space achieved to reduce indoor air temperature and relative humidity (RH) level significantly and succeeded to induce air movement in the occupied level of up to 0.38m/s in the windows and doors are kept opened case. However, although all the HTV application strategies succeeded to reduce the Operative Temperature (OT) and Standard Effective Temperature (SET*) level compared to the existing condition, the overall results revealed that it is still not able to ensure occupants’ thermal comfort level at most of the time, when the OT achieved were above the upper comfort limits of 30.0°C for about 21% to 45% during the study period. One possible improvement of the device derived from the results is by applying the HTV for both attic and occupied spaces at the same time and ensure that openings are kept opened.